Non-compliance nutritional content of imported pet food in Costa Rica - Cedeño-López, André; WingChing-Jones, Rodolfo (Agronomía Mesoamericana, 2023)
Introduction. The regulations that govern balanced pet food ensure the welfare of pets, public health, and consumer safety, making it valuable to verify the nutritional content declared on labels. Objective. To determine the compliance of the guaranteed analysis of 34 imported foods for dogs, cats, hamsters, rabbits, ornamental fish, and turtles and compare the results with the nutritional recommendations found in the literature. Materials and methods. During the months of August and December of 2018, food samples of dog (10), cat (10), ornamental fish (5), turtles (4), hamster (3), and rabbits (2) food were obtained by direct purchase at different points of sale in San José, Costa Rica. The content of moisture, crude protein (CP), ether extract (EE), crude fiber (CF), calcium, phosphorus, salt, and carbohydrates were analyzed. The average content, standard deviation, maximum and minimum value of each nutrient in each group of food were calculated according to the animal species. The individual and average values obtained were compared with the values declared on the label and the nutritional recommendations found in the literature. Results. The nutrients that presented non-compliances were: salt (27), calcium (16), and energy (14). Additionally, it was found that some foods did not declare the content of salt (14), calcium (9), and phosphorus (7). With respect to the minimum nutritional requirements, twenty-two samples presented deficiencies or excesses in at least one nutriment [carbohydrates (11) and ether extract (7)]. Conclusions. Imported balanced foods for dogs, cats, rabbits, hamsters, turtles, and ornamental fish presented non-compliances in the guaranteed content of CP, EE, CF, ME, Ca, P, and salt declared on the label. The nutritional composition of the evaluated foods limits compliance with the nutritional requirements of the animals, except for rabbits that do comply with the requirements.